Chewing Gum on Reducing Thirst in Chronic Kidney Disease Patients Undergoing Hemodialysis - Putro, Dimas Utomo Hanggoro; Asri, Nurainah Fajriati Sagita; Yulinar, Yulinar (Sarana Ilmu Indonesia (salnesia), 2025)
Restrictions on fluid intake that must be carried out in patients with chronic kidney failure can cause thirst and dry mouth. This study aimed to determine the effect of chewing gum on thirst in patients with chronic kidney failure undergoing hemodialysis. The method used was a literature review with the Google Scholar database. The keywords used were